Comparison between fixed-dose, intracoronary bolus-only versus standard weight-adjusted dose, intravenous bolus and infusion administration of abciximab in patients undergoing primary percutaneous coronary intervention - Lee, C.-H. (2011)
10.1016/j.ijcard.2010.02.017